2008
DOI: 10.1103/physrevb.78.214516
|View full text |Cite
|
Sign up to set email alerts
|

Broadening of the surface Andreev bound states band of superfluidH3e-Bon a partially specular wall

Abstract: A measurement of the surface Andreev bound states of the superfluid 3 He-B phase under different boundary conditions is presented. Transverse-acoustic impedance spectroscopy was used to determine the bandwidth of the bound states on a wall with various specularities. It was found that the band was broader for larger specularity and filled up the superfluid gap above a critical specularity. Specularity was controlled by coating the wall with thin layers of 4 He and was evaluated separately using acoustic impeda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 31 publications
0
44
0
Order By: Relevance
“…If one temporary neglects the Zeeman fields H, our system is invariant under the mirror reflection with respect to the zx-plane, as well as the time-reversal, as shown in Eq. (164). Once the Zeeman fields are applied, the mirror symmetry is lost, but a combination of the mirror reflection and the time-reversal is still preserved if H y = 0.…”
Section: Promising Examples Of Topological Crystalline Superconductorsmentioning
confidence: 99%
See 3 more Smart Citations
“…If one temporary neglects the Zeeman fields H, our system is invariant under the mirror reflection with respect to the zx-plane, as well as the time-reversal, as shown in Eq. (164). Once the Zeeman fields are applied, the mirror symmetry is lost, but a combination of the mirror reflection and the time-reversal is still preserved if H y = 0.…”
Section: Promising Examples Of Topological Crystalline Superconductorsmentioning
confidence: 99%
“…At the weak coupling limit, the planar is energetically degenerate to the A-phase that is the time-reversal symmetry breaking phase with point nodes, while the strong coupling effect that is the spin-fluctuation feedback effect can stabilize the A-phase relative to the planar phase and the A-B phase boundary becomes the first order transition. The pair breaking effect and the enhancement of the surface density of states due to the surface bound state have been observed by several experiments, by using the NMR techniques [112,113,114,115,116,117,118,155,156,157], the motion of a vibrating wire resonator [158], transverse acoustic impedance [162,163,164,165,166,167,168,169], surface contributions of the heat capacity [160], and anomalous attenuation of transverse sound [161]. Among them, Murakawa et al [165,168] has observed the specularity dependence of the surface density of states by systematically controlling the surface specularity by coating the surface with 4 He layers.…”
Section: Thermodynamics In the Absence Of Dipole-dipole Interactionmentioning
confidence: 99%
See 2 more Smart Citations
“…The surface roughness can be controlled experimentally by coating the surface with 4 He atoms [30]. The angular momenta L MJ and L cont can be suppressed by the different rates as a function of the surface roughness.…”
mentioning
confidence: 99%